1997
DOI: 10.1105/tpc.9.9.1673
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein with DNA binding activity from tobacco chloroplast nucleoids.

Abstract: A 41 -kD DNA binding protein with a basic pl was purified from chloroplast nucleoids in photomixotrophically cultured tobacco cells, and its amino acid sequence was determined. Using this sequence information, its cDNA (CND41) was isolated, and its nucleotide sequence was determined. The predicted amino acid sequence of CND41 has a transit peptide of 120 amino acids and a mature protein of 382 amino acids. A distinctive helix-turn-helix motif in the lysine-rich N-terminal region of the mature protein and an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 32 publications
3
69
0
2
Order By: Relevance
“…Previous research indicated that CND41 has DNA-binding as well as aspartic protease activity. Our attempts to identify the physiological functions of CND41 using antisense CND41 tobacco lines (line R28 contained approximately 50% of the CND41 protein found in the wild type, and line R22 accumulated approximately 20%) indicated that both transformants contained more chlorophyll and showed retarded senescence of old leaves at flowering time compared with the wild type (Nakano et al 1997(Nakano et al , 2003. This gave rise to the hypothesis that CND41 has a function in protein turnover in senescent leaves.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous research indicated that CND41 has DNA-binding as well as aspartic protease activity. Our attempts to identify the physiological functions of CND41 using antisense CND41 tobacco lines (line R28 contained approximately 50% of the CND41 protein found in the wild type, and line R22 accumulated approximately 20%) indicated that both transformants contained more chlorophyll and showed retarded senescence of old leaves at flowering time compared with the wild type (Nakano et al 1997(Nakano et al , 2003. This gave rise to the hypothesis that CND41 has a function in protein turnover in senescent leaves.…”
Section: Introductionmentioning
confidence: 93%
“…Samsun NN; lines R22, R28) plants with a reduced amount of CND41 were used in this experiment (Nakano et al 1997). Transgenic tobacco transformed with modified pBI121 vector in which the b-glucuronidase gene was removed was used as the control (X6).…”
Section: Plant Materials and Nitrogen Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other DNA-binding, chloroplast nucleoid proteins have been previously described, PEND, CND41, and DCP68 (Sato et al 1993;Nakano et al 1997;Chi-Ham et al 2002). While currently nothing is known about the effects of phosphorylation on PEND and CND41, dephosphorylation by alkaline phosphatase affects the binding of purified DCP68 to DNA in vitro (Chi-Ham et al 2002).…”
Section: Discussionmentioning
confidence: 93%
“…2b). Other plant aspartic proteases that lack the plant-specific insert have been found in some plants such as rice [47], tobacco [48] and members of the Arabidopsis family [46]. CPA63 also possesses a putative signal peptide sequence (fig.…”
Section: Discussionmentioning
confidence: 99%